Exploitation of Scavenger Receptor, Macrophage Receptor with Collagenous Structure, by Cryptococcus neoformans Promotes Alternative Activation of Pulmonary Lymph Node CD11b+ Conventional Dendritic Cells and Non-Protective Th2 Bias - Xu, Jintao; Flaczyk, Adam; Neal, Lori M.; Fa, Zhenzong; Cheng, Daphne; Ivey, Mike; Moore, Bethany B.; Curtis, Jeffrey L.; Osterholzer, John J.; Olszewski, Michal A. (Frontiers in Immunology, 2017)
Macrophage receptor with collagenous structure (MARCO) contributes to fungal containment during the early/innate phase of cryptococcal infection; however, its role in adaptive anti-fungal immunity remains unknown. Using a murine model of cryptococcosis, we compared host adaptive immune responses in wild-type and MARCO-/- mice throughout an extended time course post-infection. Unlike in early infection, MARCO deficiency resulted in improved pulmonary fungal clearance and diminished cryptococcal dissemination during the efferent phase. Improved fungal control in the absence of MARCO expression was associated with enhanced hallmarks of protective Th1-immunity including: higher frequency of pulmonary TNFa-producing T cells; increased cryptococcal-antigen-triggered IFNg and TNFa production by splenocytes and enhanced expression of M1 polarization genes by pulmonary macrophages. Concurrently, we found lower frequencies of IL-5 and IL-13 producing T cells in the lungs, impaired production of IL-4 and IL-10 by cryptococcal antigen-pulsed splenocytes, and diminished serum IgE, which were hallmarks of profoundly suppressed efferent Th2 responses in MARCO deficient mice compared to WT mice. Mechanistically, we found that MARCO expression facilitated early accumulation and alternative activation of CD11b+ conventional DC in the lung-associated lymph nodes (LALNs), which contributed to the progressive shift of the immune response from Th1 towards Th2 at the priming site (LALNs) and local infection site (lungs) during the efferent phase of cryptococcal infection. Taken together, our study shows that MARCO can be exploited by the fungal pathogen to promote accumulation and alternative activation of CD11b+ cDC in the LALN, which in turn alters Th1/Th2 balance to promote fungal persistence and dissemination.